The Effects of Tax Waivers, Concessionary Tax Rates, Tax Holidays, Tax Exemptions, and Free Zone Industries on Economic Growth - Lambon, Justice Iddrisu; Ocansey, Evans O. N. D. (International Journal of Economics and Financial Issues, 2026)
The main objective of this study is to empirically assess the differential impacts of various tax incentive instruments on economic growth using robust quantitative methods. Specifically, the study evaluates how each tax policy variable contributes to or detracts from national economic performance while controlling for trade openness, inflation, government expenditure, and foreign direct investment. Utilizing a panel dataset of 49 Sub-Saharan African countries, the study employs a dynamic panel regression model estimated through Panel EGLS with random effects. Descriptive statistics, correlation matrices, stationarity tests, and multicollinearity checks were conducted to ensure the reliability of the data. The findings reveal that concessionary tax rates and trade openness have significant positive effects on economic growth, while tax waivers and tax exemptions exhibit negative or insignificant relationships. Tax holidays and free trade zones show no meaningful impact, highlighting inefficiencies in policy design and implementation. These results suggest that not all tax incentives are equally effective; therefore, governments should adopt more targeted and performance-based fiscal policies. The study contributes to the ongoing policy discourse on tax reform and offers practical implications for both fiscal policymakers and accounting researchers.